Estimasi Nilai Ekonomis Sisa Makanan Melalui Pendekatan Perilaku Konsumen - Kustiawati Ningsih; Sustiyana Sustiyana; Mahtumia Mahtumia (JSEP (Journal of Social and Agricultural Economics), 2023)
One of the important food issues to pay attention to is food waste. Restaurants have a high contribution in producing the amount of leftover food. The restaurant is one of the places that is visited by the public every day from various circles. The high level of buying and selling activity can cause an increase in the amount of food waste heaps. This study aims to: (1) analyze the influencing factors of uneaten food at Kedai Makan Garasi in Pamekasan City and (2) estimate the amount and economic value of unconsumed food at Kedai Makan Garasi in Pamekasan City. The method used is logistic regression analysis, descriptive analysis, and survey methods. This study uses primary data and secondary data. The sampling method in this study used a non-probability sampling method. In this study, the number of samples taken was 55 respondents. The results showed that the factors that significantly influenced the behavior of leaving food at Kedai Garasi were gender. Food waste from consumer plates is dominated by vegetable and complementary side dishes, which is 27 percent. The total economic value due to food waste from 32 consumers reaches Rp. 12,759,344 per year, and Rp. 428,700,000 per year from the projected garage shop. As well as the value of economic losses due to food waste from food waste on consumers' plates reaches 12.7 million rupiah per year.